Laboratory Examination in Tonsillitis: A Literature Review - Sembiring, Dustin Delano Pranata; Imanto, Mukhlis; Sangging, Putu Ristyaning Ayu; Angraini, Dian Isti (Medula, 2024)
Laboratory tests play a crucial role in the diagnosis and etiology of tonsillitis, especially in children. Tonsillitis, an inflammation of the palatine tonsils, commonly affects children aged 5–15 years and is a significant cause of morbidity associated with upper respiratory tract infections. The disease can be classified into acute and chronic tonsillitis based on duration, with causes varying from viral to bacterial infections. Laboratory parameters such as leukocyte, neutrophil, lymphocyte, platelet counts, and C-reactive protein are used to differentiate the etiology of tonsillitis. Bacterial tonsillitis generally shows an increase in leukocytes and neutrophils, while viral infections are more commonly associated with lymphocytosis. Complete blood count, throat culture, and rapid antigen detection test (RADT) are the mainstays of diagnostic testing. Throat culture is considered the gold standard for pathogen identification, although it is more time-consuming. RADT offers a faster alternative with high sensitivity and specificity. Anti-Streptolysin O (ASO) titer is also important to detect Group A β-hemolytic Streptococcus infection, which is often associated with chronic tonsillitis. Recent studies have shown a correlation between laboratory results and the severity of tonsillitis. For example, a study in Sudan found that 64% of patients with tonsillitis had neutrophilia, 54% showed an elevated erythrocyte sedimentation rate, and 50% were ASO positive. These findings confirm the association between bacterial infection and chronic tonsillitis. However, interpretation of laboratory results must be done with caution, considering factors such as the time of sampling, examination technique, patient age, and the skill of the health care provider. Appropriate clinical decision-making requires the integration of laboratory results with the patient's clinical history. Further research is needed to explore the correlation between laboratory parameters, the severity of tonsillitis, and their impact on optimal therapy choices. A better understanding of these relationships will help improve the accuracy of diagnosis and the effectiveness of tonsillitis treatment.